Rancang Bangun Sistem Penyewaan Trucking PT Puma Logistic Menggunakan Metode Activity based Costing - Nur Huda, Riki; Sidqon, Mochamad (Jurnal Rekayasa Sistem Informasi dan Teknologi, 2024)
The development of technology in modern times is very useful for the corporate environment in order to facilitate the management of a company's data. one of them is a company engaged in the rental of trucking vehicles. This research aims to create a website-based trucking rental information system using the Activity Based Costing method to determine rental prices. At this stage, testing was carried out with 18 cases in blackbox testing with success in all test situations. With an approach using the Activity Based Costing method, it can help in obtaining more detailed cost calculations and increasing the accuracy of cost calculations based on activities. Thus this research provides benefits for determining rental prices based on activities that affect costs and with sea data management in the company.